The Impact of Digitization on Green Innovation Performance: Evidence Based on Panel Data of 228 Prefectural-Level Cities in China. (15th July 2022) - Jia, Lijiang; Hu, Xiaoli; Zhao, Zhongwei; Zhou, Tianze; Liu, Weiming; He, Bin
Abstract : At present, in the context of the era of energy and digital reform enabling the "dual carbon" goal, in order to improve the performance of urban green innovation, digitalization has become more and more important. Based on panel data, taking 228 prefecture-level cities in China from 2003 to 2019 as an example, this study expounds three dimensions of promoting green innovation performance in the internal mechanism of digital development: direct transmission mechanism, indirect transmission mechanism, and regional heterogeneity transmission mechanism. This article uses mechanism analysis and adopts a dynamic spatial panel model and systematic GMM method to empirically test the growth effect of green innovation performance endowed by digitization. This article found that green innovation performance showed regional heterogeneity and urban heterogeneity after adding carbon dioxide emissions from energy consumption, and digital development significantly improved the level of innovation performance. Further research found that digitalization has a positive impact on technological innovation, and technological innovation also has a positive impact on green innovation performance. And technological innovation plays a mediating role between digitalization and green innovation performance. Different intensities of environmental regulation play a positive moderating role in the impact of digitalization on green innovation performance.